Efeito túnel multidimensional em reações nucleares - Agrello, Deise Amaro [UNESP] (1992)
The quantum tunneling through a potential barrier in several dimensions is discussed and three diferent problems are studied. Firstly the tunneling problem through two dimensional barrieers is studied using quantum mechanical methods. We consider the collision of two Ni isotopos at energies near the top of the barrier of 100 Mev. The reflection and transmission coefficients are found through a coupled channel calculation. We have considered up to five open channels in the numerical calculations and have found that if the number of channels is increased further the results change only slightly. A different kind of coupling between the degrees of freedom from those found in the literature is proposed and the effect of this coupling in the barrier region is studied. The sub-barrier fusion reaction cross section is also calculated and our results are compared with the data and other results found in the literature. The second problem is the spontaneous emission of nuclei havier than the alpha particle. The emission of 'INTPOT. 14 C' from 'INTPOT. 223 Ra' recently observed is discussed and the penetrability factors are calculated. The ratio of the preformation factor for the'INTPOT. 14 C' emission relative to the emission of the alpha particles by the 'INTPOT. 223 Ra' is studied. Considering a realistic potential barrier we compare our results for penetrability factors and preformation factors with other recently found in the literature. Then, the size of the nuclear radius in the exotic decay theory is studied, considering several reactions where decays of nuclei heavier than the alpha particle have been observed. Finally the alpha clustering in nuclei is considered. Using a simple cluster model some nuclear properties of the 'INTPOT. 43 Ti' are studied, as wave functions, energy levei schemes and decay widths. Two different kinds of semiclassical approximations are considered to study the wave functions and the quantum...